2023
DOI: 10.2337/db23-0355
|View full text |Cite
|
Sign up to set email alerts
|

PTPN2 Regulates Metabolic Flux to Affect β-Cell Susceptibility to Inflammatory Stress

Yong Kyung Kim,
Youngjung Rachel Kim,
Kristen L. Wells
et al.

Abstract: Protein tyrosine phosphatase N2 (Ptpn2) is a type 1 diabetes (T1D) candidate gene identified from human genome-wide association studies. PTPN2 is highly expressed in human and murine islets and becomes elevated upon inflammation and models of T1D, suggesting that PTPN2 may be important for beta cell survival in the context of T1D. To test whether PTPN2 contributed to beta cell dysfunction in an inflammatory environment, we generated a beta cell-specific deletion of Ptpn2 in mice (Ptpn2 βKO). While unstressed a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…That study reported that increased tyrosyl phosphorylation of ACLY caused a detrimental effect on metabolic activity and insulin secretion, a result that could be attributed to both its role in the generation of acetyl‐CoA and regulation of gene expression. Furthermore, the observed changes were compounded by a reduction in citrate production 48 (Figure 3). Several inhibitors targeting ACLY have also shown promising outcomes in diverse therapeutic areas, demonstrating that inhibition of ACLY has the potential to modulate inflammation and reduce the progression of atherosclerotic diseases 49 (Figure 3).…”
Section: Dependence Of Histone Acetylation On Metabolic Intermediatesmentioning
confidence: 99%
See 1 more Smart Citation
“…That study reported that increased tyrosyl phosphorylation of ACLY caused a detrimental effect on metabolic activity and insulin secretion, a result that could be attributed to both its role in the generation of acetyl‐CoA and regulation of gene expression. Furthermore, the observed changes were compounded by a reduction in citrate production 48 (Figure 3). Several inhibitors targeting ACLY have also shown promising outcomes in diverse therapeutic areas, demonstrating that inhibition of ACLY has the potential to modulate inflammation and reduce the progression of atherosclerotic diseases 49 (Figure 3).…”
Section: Dependence Of Histone Acetylation On Metabolic Intermediatesmentioning
confidence: 99%
“…The regulation of ACLY has predominantly been investigated in the context of cancer cells, where it is activated by acetylation and AKT‐mediated phosphorylation, and degraded by ubiquitinylation 47 . Recently, in β‐cells, ACLY has been identified as a novel substrate for PTPN2 48 . That study reported that increased tyrosyl phosphorylation of ACLY caused a detrimental effect on metabolic activity and insulin secretion, a result that could be attributed to both its role in the generation of acetyl‐CoA and regulation of gene expression.…”
Section: Dependence Of Histone Acetylation On Metabolic Intermediatesmentioning
confidence: 99%